2018
DOI: 10.33549/physiolres.933463
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Skin Glycosaminoglycans to the Regulation of Sodium Homeostasis in Rats

Abstract: The glycosaminoglycan (GAG) molecules are a group of high molecular weight, negatively charged polysaccharides present abundantly in the mammalian organism. By their virtue of ion and water binding capacity, they may affect the redistribution of body fluids and ultimately the blood pressure. Data from the literature suggests that the mitogens Vascular Endothelial Growth Factor (VEGF)-A and VEGF-C are able to regulate the amount and charge density of GAGs and their detachment from the cell surface. Based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…An increase in total GAGs and a relative increase in sGAGs was also found in patients with heart failure with increased tissue water content and peripheral (extracellular) oedema and thus tissue Na + content (Nijst et al., 2018). Other studies have shown that the amount of GAGs with Na + ‐binding capacity correlates positively with skin Na + content in humans (Fischereder et al., 2017), as well as rats (Kopp et al., 2018; Sugar et al., 2018), all suggesting an active role for GAGs in Na + storage. We have no explanation for our finding that sGAGs were unaffected by salt load.…”
Section: Discussionmentioning
confidence: 93%
“…An increase in total GAGs and a relative increase in sGAGs was also found in patients with heart failure with increased tissue water content and peripheral (extracellular) oedema and thus tissue Na + content (Nijst et al., 2018). Other studies have shown that the amount of GAGs with Na + ‐binding capacity correlates positively with skin Na + content in humans (Fischereder et al., 2017), as well as rats (Kopp et al., 2018; Sugar et al., 2018), all suggesting an active role for GAGs in Na + storage. We have no explanation for our finding that sGAGs were unaffected by salt load.…”
Section: Discussionmentioning
confidence: 93%
“…Relative content of skin HA disaccharides was measured by HPLC-MS as previously described (Sugar et al, 2018).…”
Section: Liquid Chromatography-mass Spectrometrymentioning
confidence: 99%
“…The amount of skin Na + -binding GAGs positively correlates with skin Na + content (Fischereder et al, 2017;Sugar et al, 2018). High salt consumption increases Na + content as well as the amount of GAGs of the skin (Titze et al, 2003(Titze et al, , 2004, while in salt depletion, both of them decrease (Schafflhuber et al, 2007;Sugar et al, 2018;Lopes-Menezes et al, 2019). Consensus holds that the Na + storage mediated by GAGs is an actively regulated process.…”
Section: Introductionmentioning
confidence: 99%
“…If a microangiopathy and interstitial fluid bound to glycosaminoglycans are present early in lipedema tissue, treatment should aim at supporting the vessels in the legs by the use of the following: compression garments; hands on therapy to move fluid, sodium, and Allen, et al; Women's Health Reports 2020, 1.1 http://online.liebertpub.com/doi/10.1089/whr.2020.0086 other prelymph components out of the tissue into lymphatic vessels; flavonoids and other anti-inflammatories from food and supplements to help reduce inflammation of the microvessels 32 ; and possibly a low-salt diet to decrease glycosaminoglycan content. 31 The data in this article were based on an AVP and collagen spacing that if incorrect as markers of leaky vessels and increased interstitial fluid, respectively, would negate our findings. However, our phenotype was based on published data demonstrating perivascular spaces around capillaries in fat tissue in lipedema, 12 perivascular spaces, 11 and spaces between collagen fibers in the dermis 24 in lymphedema, perivascular immune cell infiltrate in the skin in lipedema, 8,19 and endothelial cell rounding as a marker of increased paracellular transport.…”
Section: Discussionmentioning
confidence: 59%